1992
DOI: 10.2169/internalmedicine.31.994
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in Patients with Arteriosclerosis Obliterans of the Lower Extremities or Aortic Aneurysm.

Abstract: Routine coronary angiography was performed in order to determine the incidence and clinical condition of coronary artery disease in 37 patients with arteriosclerosis obliterans or aortic aneurysm. Coronary angiography demonstrated significant stenosis in 12 (57%) of 21 patients with arteriosclerosis obliterans and in 7 (44%) of 16 patients with aortic aneurysm. The prevalence of risk factors for arteriosclerosis was similar for patients with arteriosclerosis obliterans and those with aortic aneurysm, and simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…and pertinent information including year the case series was published, number of patients, gender, age, cardiac risk factors, peripheral vascular territory involved, and coronary angiographic data were collected and tabulated (Table 4). The 19 case series included patients undergoing elective surgery for abdominal aortic aneurysms 4,7,9,10,15,17,18,20,21,23 , lower extremity arterial lesions 12 , a combination of abdominal aortic aneurysm and lower extremity arterial lesions 8,11,22 , a combination of abdominal and thoracic aortic aneurysms 16 , carotid artery disease 5,14 , a combination of abdominal aortic aneurysm and aortoiliac disease 19 , and a combination of all territories including other areas such as renal and mesenteric arterial disease 13 (Table 4). Except for one series 4 that reported a predominance of women similar to ours, the vast majority of patients in the remaining 19 case series were men.…”
Section: Resultsmentioning
confidence: 99%
“…and pertinent information including year the case series was published, number of patients, gender, age, cardiac risk factors, peripheral vascular territory involved, and coronary angiographic data were collected and tabulated (Table 4). The 19 case series included patients undergoing elective surgery for abdominal aortic aneurysms 4,7,9,10,15,17,18,20,21,23 , lower extremity arterial lesions 12 , a combination of abdominal aortic aneurysm and lower extremity arterial lesions 8,11,22 , a combination of abdominal and thoracic aortic aneurysms 16 , carotid artery disease 5,14 , a combination of abdominal aortic aneurysm and aortoiliac disease 19 , and a combination of all territories including other areas such as renal and mesenteric arterial disease 13 (Table 4). Except for one series 4 that reported a predominance of women similar to ours, the vast majority of patients in the remaining 19 case series were men.…”
Section: Resultsmentioning
confidence: 99%
“…Lower extremity arteriosclerosis obliterans (LEASO) is a chronic progressive disease, in which atherosclerosis causes thickening of the intima of lower extremity arteries, narrowing or even occlusion of the lumen, and further causes a series of symptoms and signs of the affected limb, such as intermittent claudication, resting pain and even ulcer necrosis (Gao et al, 2010). It was reported that the proportion of LEASO complicated with coronary artery disease was significantly higher than that of other diseases, as high as 70% (Aoshima et al, 1992). Atherosclerosis, especially LEASO, is a complex inflammatory disease process that is the major underlying cause of coronary artery disease (Seibert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%